An Account of the Excavation of a Dwelling of the Viking Period at ’Jarlshof,’ Sumburgh, Shetland, carried out on behalf of H.M. Office of Works - Curle, Alexander O (Proceedings of the Society of Antiquaries of Scotland, 1935)